Perceptions of individuals with autism spectrum disorder (ASD) and their parents about the needs and the role of occupational therapy in the transition of these individuals into the labour market - Mhlekwa, Bonang Sylvia (My University, 2021)
South Africa, like other regions of the world has a high rate of autism spectrum disorder (ASD) (Bateman, 2013). Young adults with ASD disproportionally achieve lower rates of independent functioning and interpersonal success in occupation and other domains compared to similar aged peers without the disorder (Hendricks, 2010; Hume, et al., 2009, Mazurek, 2014). The transitions of these individuals in the labour market is of concern since there is a lack of services for adults with ASD and research indicates they achieve an average employment rate of 49%, even in developed countries (Howlin and Moss, 2012). The objective of this study was to explore the perceptions of individuals with ASD who have finished their formal education or training and their parents in terms of their unmet needs in relation to transitioning into the labour market. The study will also explore their perceptions about the role an occupational therapist can play in addressing these unmet needs and facilitating their transition into the labour market. A qualitative explorative descriptive research method was used to explore perceptions of individuals with ASD and those of their parents using a phenomenological approach by exploring the lived experience transitioning to employment (Creswell. 2014:239). Semi-structured, face to face interviews were used with parents of individuals with ASD, while email interviews were used with individuals with ASD to collect data. Data was analysed using inductive thematic analysis to develop themes, categories and codes. Two broad themes were identified namely “Transitioning was really hard”, and “Occupational therapists can do more”. The findings emphasised the difficulties in finding and keeping a job, parents needs as well as the perception of and the suggestions for the role of occupational therapy. Findings indicate that occupational therapists should develop vocational rehabilitation programs specifically for adolescents with ASD that can be implemented during transition process. These programs should include; case management, advocacy, skills training, and job coaching. Supported employment and advocacy in terms of employer education is also indicated as a role, occupational therapists could play.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science in Occupational Therapy to the Faculty of Health Sciences, School of Therapeutic Sciences, University of the Witwatersrand, Johannesburg, 2021